Does Research Influence Educational Policy? The Perspective of Researchers and Policy-Makers in Romania - Ion, Georgeta; Iucu, Romiţă (The European Higher Education Area: Between Critical Reflections and Future Policies, 2015)
The aim of the paper is to analyze the relationship between educational research and its use in the policy-making process in Romania. We examine the ways in which research influences educational policy, the mechanisms by which this influence operates and whether it can be improved. We focus firstly upon research production, looking to identify the researchers’ perception regarding the quality and the potential of their research with respect to the policy-making process. Secondly, we analyze policy makers’ opinions regarding research and its incorporation into policy-making. Finally, we discuss the obstacles and opportunities presented by the transfer of research into policy making, and make some suggestions as to how this can be improved. We used qualitative methods based on in-depth interviews with researchers and policy-makers in Romania. The results show that, in general, policy makers are not using research results, and we identify the causes of this situation. We identify different types of causes, from the quality and visibility of research activity to the structural and institutional obstacles which research activity and transfer have to face. The implications are discussed at three different levels: the micro level represented by the individual researcher, the mezzo level, represented by the organization and the macro level – the systemic context. The conclusions offer researchers and policy-makers opportunities to consider opportunities and constraints, in order to improve the relationship between the educational research and its potential users.